Chicken Feed Processing Machines Using Autodesk Inventor Software - Sabaruddin Syach; Noer Aden Bahry; Anis Siti Nurrohkayati (Procedia of Engineering and Life Science, 2021)
In chicken farm, the biggest cost is from chicken feed. The feed cost is too expensive because it uses factory feed, which makes operational costs high, then the profits obtained are very small. The idea is to make the design of a chicken feed processing machine to increase the efficiency of chicken feed costs. The owner of chicken farm can produce chicken feed itself. This chicken feed processing machine is equipped with a corn grinder, dough mixer, and chicken feed mold. This chicken feed processing machine in chicken feed printing has a screw conveyor working principle that utilizes the threads of the screw as a material carrier and presses towards the end of the mold and is cut using 2 rotating blades following the screw conveyor rotation. The chicken feed processing machine uses an electric motor that has a power of 1.5 Hp with a rotation of 140 rpm and can produce 20.16 kg/hour of chicken feed. This machine has dimensions of 125 cm x 40 cm x 80 cm, the chicken feed processing machine designed using Autodesk Inventor software.